2018
DOI: 10.1016/j.tsf.2018.09.026
|View full text |Cite
|
Sign up to set email alerts
|

In vacuo XPS investigation of Cu(In,Ga)Se2 surface after RbF post-deposition treatment

Abstract: Latest record efficiencies of Cu(In,Ga)Se2 (CIGSe) solar cells were achieved by means of a rubidium fluoride (RbF) post-deposition treatment (PDT). To understand the effect of the RbF-PDT on the surface chemistry of CIGSe and its interaction with sodium that is generally present in the CIGSe absorber, we performed an X-ray photoelectron spectroscopy (XPS) study on CIGSe thin films as-deposited by a three-stage co-evaporation process and after the consecutive RbF-PDT. The sample transfer from the deposition to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
32
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 20 publications
10
32
1
Order By: Relevance
“…With the methods utilized in this study we could not detect the formation of an RbInSe 2 phase after an RbF‐PDT of an In 2 Se 3 layer. However, a more surface‐sensitive comparison of the chemical environment of the Rb‐atoms in our RbInSe 2 sample with the one of an RbF‐treated CIGS thin film shows good agreement . The fact that both theoretical and experimental results show a higher bandgap energy for RbInSe 2 compared to the one of In 2 Se 3 and CIGS is supporting the hypothesis that interface recombination at the CIGS/CdS junction could be reduced due to the formation of RbInSe 2 during an RbF‐PDT.…”
Section: Composition Of the Thin Films As Measured By Xrf After Rinsisupporting
confidence: 76%
See 2 more Smart Citations
“…With the methods utilized in this study we could not detect the formation of an RbInSe 2 phase after an RbF‐PDT of an In 2 Se 3 layer. However, a more surface‐sensitive comparison of the chemical environment of the Rb‐atoms in our RbInSe 2 sample with the one of an RbF‐treated CIGS thin film shows good agreement . The fact that both theoretical and experimental results show a higher bandgap energy for RbInSe 2 compared to the one of In 2 Se 3 and CIGS is supporting the hypothesis that interface recombination at the CIGS/CdS junction could be reduced due to the formation of RbInSe 2 during an RbF‐PDT.…”
Section: Composition Of the Thin Films As Measured By Xrf After Rinsisupporting
confidence: 76%
“…However, based on these results, no direct conclusion can be drawn on the formation of RbInSe 2 during the RbF‐PDT of CIGS. Nonetheless, as a result of an earlier X‐Ray Photoelectron Spectroscopy (XPS) investigation a good match of the Rb 3d core level binding energies was already shown between the same RbInSe 2 sample discussed here to those of RbF‐treated CIGS . We also investigated the formation of intrinsic defects in RbInSe 2 .…”
Section: Composition Of the Thin Films As Measured By Xrf After Rinsisupporting
confidence: 53%
See 1 more Smart Citation
“…[43] We have shown that even a small change in the spike at the CIGS/CdS interface, when combined with the CdS/ZnO cliff, can also significantly affect the current transport. Accumulation of alkali metals and fluoride [22,44] could also change this band lineup via the formation of dipoles. A formation of an alkali-In-Se layer at the surface of the absorber after PDT [5,7,21,22] might also lead to a change in the band lineup to the buffer layer.…”
Section: Discussionmentioning
confidence: 99%
“…The formation of secondary phases such as RbInSe 2 has been described at the CIGS surface during PDT and interpreted as the layer responsible for the surface bandgap increase in the absorber. [5,[20][21][22] As the goal here is to understand the principle mechanisms of limited current transport across the interface, no such layer has been explicitly added to the models. However, the main effects of such a layer would be a change in the band offsets and local doping which are considered in our model.…”
Section: Introductionmentioning
confidence: 99%